QOLP-25. QUALITY OF LIFE FOLLOWING RE-IRRADIATION FOR RECURRENT HIGH GRADE GLIOMA. (5th November 2018) - Amidei, Christina; Dixit, Karan; Kumthekar, Priya; Kruser, Tim; Sachdev, Sean; Kalapurakal, John; Gondi, Vinai; Grimm, Sean; Nicholas, Martin; Lukas, Rimas; Chmura, Steven; Mehta, Minesh; et al.
Abstract: BACKGROUND: Re-irradiation has recently garnered interest as a treatment option for recurrent high grade glioma. Evidence supporting benefits in this population is evolving, but little is known about impact on quality of life (QOL). QOL patient reports were collected in a phase II hypofractionated re-irradiation study. METHODS: Patients with recurrent anaplastic glioma or glioblastoma were stratified into four groups based on histology and prior bevacizumab exposure. Treatment consisted of 45 Gy radiation delivered in 25 fractions with daily temozolomide 75 mg/m2 and bevacizumab 10 mg/kg every 2 weeks. This was followed by adjuvant daily temozolomide 50 mg/m2 for 6 weeks and bevacizumab 10 mg/kg every 2 weeks in an 8 week cycle for up to 6 cycles, or until progression or intolerance. FACT-Brain and FACIT-Fatigue were collected as secondary end-point data prior to treatment start, at end of the concurrent phase, and after each cycle. RESULTS: Of 54 patients treated, 42 (78%) had evaluable QOL data. Mean baseline FACT-Br and FACIT-Fatigue scores were within expected ranges for persons with brain tumors. Significant declines were noted in FACT-Br Total (p=0.4), FACT-Br TOI (p=.05) and FACIT-Fatigue (p<.01) at the end of concurrent treatment, but FACT-Br Total and FACT-Br TOI scores rebounded to baseline level by end of cycle 1 and were maintained at cycle 2 end. Fatigue scores improved after cycle 1 but did not return to baseline until after cycle 2. CONCLUSION: Re-irradiation with temozolomide and bevacizumab is associated with decline in QOL immediately after concurrent treatment but QOL improves over time. This QOL pattern is similar to that seen with initial radiation treatment and suggests that re-irradiation does not progressively adversely affect QOL for at least the first four months after treatment.